Metal-glass fiber reinforced thermoplastic resin composite material

By adjusting the hot-melt temperature difference and long diameter ratio of glass fiber, and controlling the content of glass, the metal-glass fiber enhanced thermoplastic resin composite material low heat resistance and cycle-resistant cyclicicity Excellent heat resistance and cyclic comprehensive effect.

CN119365335APending Publication Date: 2025-01-24NITTO BOSEKI CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280096307.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2022-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In metal-glass fiber reinforced thermoplastic resin composites, the expansion-contraction of the thermoplastic resin leads to interface peeling, reducing the heat cycle resistance of the material. At the same time, there are also adverse conditions in the productivity and mechanical strength of the glass fiber.

Method used

By adjusting the difference ΔT between the 500 poise temperature and the 10,000 poise temperature of the glass fiber to 157 to 186°C, and the ratio A of the long diameter to the short diameter of the glass fiber to the range of 1.5 to 4.5, combined with 20.0 to 65.0 mass% With a high glass content, a metal-glass fiber reinforced thermoplastic resin composite material with excellent heat cycle resistance is prepared.

Benefits of technology

It achieves high productivity of glass fiber and high mechanical strength of reinforced thermoplastic resin material while maintaining excellent heat cycle resistance between metal and glass fiber reinforced thermoplastic resin material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143316890000251
    Figure BDA0005143316890000251
  • Figure BDA0005143316890000252
    Figure BDA0005143316890000252
  • Figure BDA0005143316890000261
    Figure BDA0005143316890000261
Patent Text Reader

Abstract

Provided is a metal-glass fiber-reinforced thermoplastic resin composite material which has high productivity of glass fibers, high mechanical strength of a glass fiber-reinforced thermoplastic resin material, and excellent heat cycle resistance between a metal material and the glass fiber-reinforced thermoplastic resin material. The metal-glass fiber-reinforced thermoplastic resin composite material comprises a metal material and a glass fiber-reinforced thermoplastic resin material, the difference [Delta] T between the 500 poise temperature T1 and the 10000 poise temperature T2 of the glass fibers contained in the glass fiber-reinforced thermoplastic resin material is 162-181 DEG C, and the ratio (long diameter / short diameter) (A) of the long diameter to the short diameter of the glass filaments is 1.5-4.5. The glass fiber-reinforced thermoplastic resin material has a glass content (C) of 20.0-65.0 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal-glass fiber reinforced thermoplastic resin composite material. Background Art

[0002] In the past, glass fiber has been widely used in various applications because it can improve the strength of resin materials. In recent years, the use of glass fiber reinforced resin materials has expanded to metal replacement materials, and in particular, for components requiring high mechanical strength, people have studied the use of composite materials (metal-glass fiber reinforced thermoplastic resin composite materials) formed by bonding and integrating metal materials and glass fiber reinforced thermoplastic resin materials (for example, refer to Patent Documents 1 and 2).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-161693

[0006] Patent Document 2: International Publication No. 2020 / 004597 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, in the above-mentioned metal-glass fiber reinforced thermoplastic resin composite material, as the thermoplastic resin expands and contracts, submicron-level interface peeling is easily generated at the interface between the above-mentioned metal material and the above-mentioned glass fiber reinforced thermoplastic resin material, and there is an undesirable situation that the bonding strength (also called heat cycle resistance) between the above-mentioned metal material and the above-mentioned glass fiber reinforced thermoplastic resin material is low when a heat cycle is applied.

[0009] Furthermore, depending on the type of glass fiber used, although the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material is improved, there are disadvantages such as deterioration in productivity of glass fiber or reduction in mechanical strength of the glass fiber reinforced thermoplastic resin material.

[0010] The object of the present invention is to eliminate the above-mentioned undesirable conditions and provide a metal-glass fiber reinforced thermoplastic resin composite material having high productivity of glass fiber, high mechanical strength of glass fiber reinforced thermoplastic resin material, and excellent heat cycle resistance between metal material and glass fiber reinforced thermoplastic resin material.

[0011] Means for solving problems

[0012] In order to achieve the above-mentioned object, the technical content of the metal-glass fiber reinforced thermoplastic resin composite material of the present invention is as follows. The metal-glass fiber reinforced thermoplastic resin composite material comprises a metal material and a glass fiber reinforced thermoplastic resin material located on at least one surface of the metal material, characterized in that the difference ΔT (ΔT=T1-T2) between the 500 poise temperature T1 and the 10000 poise temperature T2 of the glass fiber contained in the glass fiber reinforced thermoplastic resin material is in the temperature range of 157 to 186°C, the glass filaments constituting the glass fiber have a flat cross-sectional shape in which the ratio of the major diameter to the minor diameter (major diameter / minor diameter) A of the glass filaments is in the range of 1.5 to 4.5, and the glass content C of the glass fiber reinforced thermoplastic resin material is in the range of 20.0 to 65.0 mass %.

[0013] The metal-glass fiber reinforced thermoplastic resin composite material of the present invention has the above-mentioned structure, and the productivity of glass fiber and the mechanical strength of glass fiber reinforced thermoplastic resin material are high, and excellent heat cycle resistance between metal material and glass fiber reinforced thermoplastic resin material can be achieved.

[0014] The glass fiber can be manufactured by supplying a predetermined glass raw material (batch glass material) into a melting furnace, ejecting the melted batch glass material (molten glass) from a nozzle head or a hole, drawing and cooling the molten glass material to solidify it to form glass filaments, and bundling the glass filaments. Here, the following operation is referred to as "spinning": ejecting the molten glass material from a nozzle head or a hole, drawing and cooling the molten glass material to solidify it to form the glass filaments.

[0015] In the spinning, when the nozzle tip or hole has a non-circular shape and has a protrusion or cutout for rapidly cooling the molten glass, glass filaments having a non-circular cross-sectional shape, such as a flat cross-sectional shape, can be obtained by controlling the temperature conditions.

[0016] The metal-glass fiber reinforced thermoplastic resin composite material of the present invention can be prepared, for example, by the following method: the above-mentioned metal material is loaded into the mold of an injection molding machine, and the resin particles with a specified glass content obtained by mixing the above-mentioned glass fiber and thermoplastic resin using a twin-axis mixer are put into the injection molding machine for insert molding.

[0017] Here, the high productivity of glass fiber refers to the following situation: prescribed glass scraps are put into a platinum container, the platinum container is heated to a temperature range of 1200-1450°C to melt the glass scraps, and the obtained molten glass is pulled out from the nozzle head of the platinum container and wound on a winder, and the winder is rotated, and the molten glass is wound at a speed of 1100 rpm for 1 hour, and the spinning can be continuously carried out without interruption during the period of 1 hour. The above-mentioned glass scraps are made in the following manner: glass raw materials (glass batch materials) prepared into a prescribed glass composition are put into a platinum crucible, and the glass raw materials are kept at a temperature of 1650°C in an electric furnace for 6 hours, and the glass raw materials are melted while being stirred, thereby obtaining a homogeneous molten glass, and the molten glass is poured onto a carbon plate.

[0018] In addition, the high mechanical strength of the glass fiber reinforced thermoplastic resin material refers to the following situation: the resin pellets used in the production process of the metal-glass fiber reinforced thermoplastic resin composite material of the present invention are injection molded to produce a type A dumbbell test piece (thickness 4 mm) based on JIS K 7165:2008, and the measured value of the type A dumbbell test piece obtained by the static tensile test based on JIS K 7171:2016 under the condition of a test temperature of 23°C is in the range of 180 MPa or more.

[0019] In addition, the above-mentioned metal-glass fiber reinforced thermoplastic resin composite material has excellent heat cycle resistance between the metal material and the glass fiber reinforced thermoplastic resin material, which means that in the low and high temperature resistance test described later, within the range of 48 cycles or less, no damage occurs at the interface between the metal material and the glass fiber reinforced thermoplastic resin material of the metal-glass fiber reinforced thermoplastic resin composite material.

[0020] In the metal-glass fiber reinforced thermoplastic resin composite material of the present invention, the glass content of the above-mentioned glass fiber reinforced thermoplastic resin material can be calculated in the following manner: the glass fiber reinforced thermoplastic resin material is separated from the metal-glass fiber reinforced thermoplastic resin composite material, and the above-mentioned glass content of the separated glass fiber reinforced thermoplastic resin material is calculated according to JIS K 7052:1999.

[0021] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present invention, the glass fiber contained in the glass fiber reinforced thermoplastic resin material has a Vickers hardness H in the range of 700 to 800 HV0.2, and the A, C, ΔT and H preferably satisfy the following formula (1), and more preferably satisfy the following formula (2):

[0022] 6.53≤H×C 1 / 2 / (A×ΔT)≤13.45…(1)

[0023] 5.72≤H×C 1 / 2 / (A×ΔT)≤9.83…(2).

[0024] The Vickers hardness H of the glass fiber contained in the above-mentioned glass fiber-reinforced thermoplastic resin material can be measured by the following method.

[0025] 〔Vickers hardness H〕

[0026] First, the glass fiber reinforced thermoplastic resin material is separated from the metal-glass fiber reinforced thermoplastic resin composite material by a cutter, etc. Then, the glass fiber reinforced thermoplastic resin material is heated in a muffle furnace at a temperature range of 300 to 650° C. for about 0.5 to 24 hours to decompose the organic matter.

[0027] Next, the remaining glass fiber is placed in a platinum crucible, and the temperature is maintained at 1600°C in an electric furnace for 6 hours, and the glass fiber is melted while being stirred, thereby obtaining a homogeneous molten glass. Next, the platinum crucible containing the molten glass is taken out from the electric furnace, and the molten glass is cooled. Next, after the molten glass is taken out from the platinum crucible, in order to remove the strain of the glass, it is heated at a strain removal temperature in the temperature range of 660 to 750°C for 2 hours, and it takes 8 hours to cool it to room temperature (20 to 25°C) to obtain a glass block.

[0028] Next, a cutting machine, such as a diamond tool and a grinder, is used to process the obtained glass block into a test piece with a width of 3 mm, a length of 80 mm, and a thickness of 1 mm. Next, according to JIS Z 2244:2020, a Vickers hardness tester (manufactured by Mitutoyo Co., Ltd., trade name: HM-220) is used to measure the Vickers hardness HV0.2 at least 5 positions on the surface of the obtained test piece under the conditions of a load of 0.2 kgf and a load time of 15 seconds. Next, by calculating the average value of the obtained measured values, the Vickers hardness H of the glass fiber can be determined. It should be noted that the 0.2 part of HV0.2 represents the size of the additional load (kgf).

[0029] In the metal-glass fiber reinforced thermoplastic resin composite material of the present invention, the glass fiber contained in the above-mentioned glass fiber reinforced thermoplastic resin material has a Vickers hardness H within the above-mentioned range, and the above-mentioned A, C, ΔT and H satisfy the above-mentioned formula (1). Therefore, the productivity of the glass fiber and the mechanical strength of the glass fiber reinforced thermoplastic resin material are high, and excellent heat cycle resistance can be achieved between the metal material and the glass fiber reinforced thermoplastic resin material.

[0030] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present invention, the glass fiber contained in the above-mentioned glass fiber reinforced thermoplastic resin material has a Vickers hardness H within the above-mentioned range, and the above-mentioned A, C, ΔT and H satisfy the above-mentioned formula (2). Therefore, the productivity of the glass fiber is high, the mechanical strength of the glass fiber reinforced thermoplastic resin material is higher, and the metal material and the glass fiber reinforced thermoplastic resin material can have better heat cycle resistance.

[0031] Here, the fact that the glass fiber reinforced thermoplastic resin material has higher mechanical strength means that the measured value of the A-type dumbbell test piece obtained by the static tensile test is in the range of 190 MPa or more.

[0032] In addition, the above-mentioned metal-glass fiber reinforced thermoplastic resin composite material has better heat cycle resistance between the metal material and the glass fiber reinforced thermoplastic resin material, which means that in the low and high temperature resistance test described later, within the range of less than 168 cycles, no damage occurs at the interface between the metal material and the glass fiber reinforced thermoplastic resin material of the metal-glass fiber reinforced thermoplastic resin composite material.

[0033] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present invention, the thermoplastic resin contained in the glass fiber reinforced thermoplastic resin material is preferably a thermoplastic resin selected from the group consisting of polyphenylene sulfide, polyamide, polybutylene terephthalate, and polycarbonate, and the above-mentioned thermoplastic resin is more preferably polyphenylene sulfide or polybutylene terephthalate. DETAILED DESCRIPTION

[0034] Next, embodiments of the present invention will be described in further detail.

[0035] The metal-glass fiber reinforced thermoplastic resin composite material of this embodiment includes a metal material and a glass fiber reinforced thermoplastic resin material located on at least one surface of the metal material, the difference ΔT (ΔT=T1-T2) between the 500 poise temperature T1 and the 10000 poise temperature T2 of the glass fiber contained in the glass fiber reinforced thermoplastic resin material is in the temperature range of 157 to 186°C, the glass filaments constituting the glass fiber have a flat cross-sectional shape in which the ratio of the major axis to the minor axis (major axis / minor axis) A of the glass filaments is in the range of 1.5 to 4.5, and the glass content C of the glass fiber reinforced thermoplastic resin material is in the range of 20.0 to 65.0% by mass.

[0036] The metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment has the above-mentioned structure, and the productivity of glass fiber and the mechanical strength of glass fiber reinforced thermoplastic resin material are high, and excellent heat cycle resistance between metal material and glass fiber reinforced thermoplastic resin material can be achieved.

[0037] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the glass fibers contained in the glass fiber reinforced thermoplastic resin material become the main cause of the breakage of the glass filaments during the spinning process when the ΔT is in the temperature range exceeding 186° C. It is believed that the reason why the glass filaments break during the spinning process is as follows: since the viscosity of molten glass is sensitive to temperature changes, the viscosity of the molten glass ejected from the nozzle head changes significantly under the influence of a slight temperature change in the space near the nozzle head ejecting the molten glass.

[0038] On the other hand, if the above ΔT is in the temperature range of less than 157°C, it is impossible to produce glass filaments having a shaped cross section in which the ratio of the major diameter to the minor diameter (major diameter / minor diameter) A of the above glass filaments falls within the above range. It is believed that the reason why glass filaments having the above shaped cross section cannot be produced is that the viscosity of molten glass does not change with temperature, so the cross-sectional shape of the glass filaments is not easily shaped.

[0039] The above ΔT is preferably in the temperature range of 165 to 175°C. It should be noted that if the content of SiO2 relative to the total amount of the above-mentioned glass fiber is increased, the 10000 poise temperature T2 will increase significantly, so the above ΔT will tend to decrease. In addition, if the content of CaO relative to the total amount of the above-mentioned glass fiber is increased, the 500 poise temperature T1 will decrease significantly, so the above ΔT will tend to decrease. Therefore, the above ΔT can be adjusted by changing the content of SiO2 and CaO relative to the total amount of the above-mentioned glass fiber.

[0040] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, if the ratio of the major diameter to the minor diameter (major diameter / minor diameter) A of the glass filaments constituting the glass fibers contained in the glass fiber reinforced thermoplastic resin material exceeds 4.5, the number of breakages during the production of the glass filaments increases, and the productivity decreases. On the other hand, if the ratio of the major diameter to the minor diameter (major diameter / minor diameter) A of the glass filaments constituting the glass fibers contained in the glass fiber reinforced thermoplastic resin material is less than 1.5, the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material deteriorates.

[0041] The ratio of the major axis to the minor axis (major axis / minor axis) A of the glass filaments constituting the above-mentioned glass fiber is preferably in the range of 2.2 to 3.9, more preferably in the range of 2.4 to 3.7, further preferably in the range of 2.5 to 3.5, particularly preferably in the range of 2.8 to 3.4, and most preferably in the range of 2.9 to 3.3.

[0042] As the flat cross-sectional shape possessed by the glass filaments of the glass fiber contained in the glass fiber reinforced thermoplastic resin material constituting the present embodiment, for example, an oblong (the short side of the rectangle is replaced with a shape after the semicircle with the short side as the diameter), an ellipse and a rectangle can be cited. From the viewpoint of contributing to improving the fluidity of the glass fiber reinforced thermoplastic resin material, the above-mentioned flat cross-sectional shape is preferably an oblong. It should be noted that, here, the cross section of the glass filament refers to the cross section perpendicular to the fiber length direction of the glass filament.

[0043] The short diameter of the glass filaments with a flat cross-sectional shape used in the glass fiber reinforced thermoplastic resin material of the present embodiment is in the length range of 4.0 to 14.0 μm, and the short diameter of the glass filaments is preferably in the length range of 4.8 to 11.5 μm, more preferably in the length range of 7.5 to 10.0 μm, and further preferably in the length range of 8.1 to 9.5 μm. On the other hand, the long diameter of the glass filaments with a flat cross-sectional shape is in the length range of 12.0 to 40.0 μm, and the long diameter of the glass filaments is preferably in the length range of 19.5 to 36.0 μm, more preferably in the length range of 27.4 to 32.0 μm, and further preferably in the length range of 28.1 to 29.2 μm.

[0044] The converted fiber diameter of the glass filaments with a flat cross-sectional shape used in the glass fiber reinforced thermoplastic resin material of the present embodiment is, for example, in the length range of 5.0 to 25.0 μm, preferably in the length range of 8.0 to 22.0 μm, more preferably in the length range of 10.0 to 18.0 μm, and further preferably in the length range of 11.0 to 15.0 μm. Here, the converted fiber diameter refers to the diameter of the glass filaments with a circular cross-section: the cross-sectional area of ​​the circular cross-section is the same as the cross-sectional area of ​​the glass filaments with a flat cross-sectional shape.

[0045] The minor diameter and major diameter of the glass filaments with flat cross-sectional shape in the glass fiber reinforced thermoplastic resin material of the present embodiment can be calculated, for example, in the following manner. First, the cross section of the glass fiber reinforced thermoplastic resin material is ground. Then, the length of the major diameter and minor diameter of more than 100 glass filaments in the cross section of the above-mentioned glass fiber reinforced thermoplastic resin material is measured using an electron microscope. At this time, the longest side through the approximate center of the glass filament cross section is used as the major diameter, and the side orthogonal to the major diameter at the approximate center of the glass filament cross section is used as the minor diameter, and each length is measured. Then, by obtaining the average value of these minor and major sides, the minor diameter and major diameter of the above-mentioned glass filaments can be calculated.

[0046] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, if the glass content C of the glass fiber reinforced thermoplastic resin material exceeds 65.0% by mass, the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material deteriorates. On the other hand, if the glass content C of the glass fiber reinforced thermoplastic resin material is less than 20.0% by mass, the bending strength of the glass fiber reinforced thermoplastic resin material becomes insufficient.

[0047] The glass content C of the glass fiber reinforced thermoplastic resin material is preferably in the range of 25.0 to 52.0 mass %, more preferably in the range of 31.0 to 48.0 mass %, and even more preferably in the range of 35.0 to 45.0 mass %.

[0048] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the glass fiber contained in the glass fiber reinforced thermoplastic resin material has a Vickers hardness H in the range of 700 to 800 HV0.2, and the above A, C, ΔT and H preferably satisfy the following formula (1), and more preferably satisfy the following formula (2):

[0049] 6.53≤H×C 1 / 2 / (A×ΔT)≤13.45…(1)

[0050] 5.72≤H×C 1 / 2 / (A×ΔT)≤9.83…(2).

[0051] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the Vickers hardness H of the glass fiber contained in the above-mentioned glass fiber reinforced thermoplastic resin material is more preferably in the range of 705 to 755 HV0.2, further preferably in the range of 720 to 750 HV0.2, and particularly preferably in the range of 730 to 745 HV0.2.

[0052] It should be noted that the Vickers hardness H is greatly affected by the content of SiO2 relative to the total amount of glass fibers. If the content of SiO2 relative to the total amount of glass fibers is increased, the Vickers hardness H tends to increase. In addition, if the content of CaO relative to the total amount of glass fibers is increased, the Vickers hardness H tends to increase. Therefore, by adjusting the content of SiO2 relative to the total amount of glass fibers and further fine-tuning the content of CaO relative to the total amount of glass fibers, the Vickers hardness H can be adjusted to a desired value.

[0053] Generally speaking, glass fiber contributes more to the rigidity of a glass fiber reinforced thermoplastic resin material than thermoplastic resin, and as C increases, the rigidity of the glass fiber reinforced thermoplastic resin material increases. Therefore, it can be considered that H×C 1 / 2 The rigidity of the glass fiber reinforced thermoplastic resin material is shown. As the rigidity of the glass fiber reinforced thermoplastic resin material increases, the strength increases, but the toughness decreases, and there is a tendency for the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material to deteriorate.

[0054] A×ΔT represents the balance between the productivity of glass fiber and the heat cycle resistance of metal-glass fiber reinforced thermoplastic resin composite material. The larger the A×ΔT, the more times the glass filaments break when manufacturing the glass fiber, and therefore, the worse the productivity of the glass fiber. On the other hand, when A×ΔT is too small, there is a tendency for the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material to deteriorate.

[0055] According to the above, it can be considered that H×C 1 / 2 / (A×ΔT) represents the balance among the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material, the productivity of the glass fiber, and the strength of the glass fiber reinforced thermoplastic resin material.

[0056] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, when the glass fiber contained in the glass fiber reinforced thermoplastic resin material has a Vickers hardness H within the above-mentioned range, it is further preferred that the above-mentioned A, C, ΔT and H satisfy the following formula (3), and particularly preferably satisfy the following formula (4):

[0057] 7.04≤H×C 1 / 2 / (A×ΔT)≤9.77…(3)

[0058] 8.33≤H×C 1 / 2 / (A×ΔT)≤9.40…(4).

[0059] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the thermoplastic resin contained in the above-mentioned glass fiber reinforced thermoplastic resin material is preferably a thermoplastic resin selected from the group consisting of polyphenylene sulfide, polyamide, polybutylene terephthalate, and polycarbonate, and the above-mentioned thermoplastic resin is more preferably polyphenylene sulfide or polybutylene terephthalate.

[0060] In the glass composition of the glass fiber of the present embodiment, the content of SiO2 relative to the total amount of the glass fiber is preferably in the range of 50 to 60% by mass, and more preferably in the range of 52 to 58% by mass. If the content of SiO2 relative to the total amount of the glass fiber is less than 50% by mass, there is a tendency for the strength of the glass fiber to decrease. On the other hand, if the content of SiO2 relative to the total amount of the glass fiber exceeds 60% by mass, the viscosity of the molten glass increases, and therefore, there is a tendency for the productivity of the glass fiber to decrease. It should be noted that the glass composition of the glass fiber of the present embodiment is exactly the same as the glass composition of the glass filaments constituting the glass fiber of the present embodiment.

[0061] In addition, in the glass composition of the glass fiber of the present embodiment, the content of CaO relative to the total amount of glass fiber is preferably in the range of 14 to 32% by mass, more preferably in the range of 18 to 28% by mass, and further preferably in the range of 20 to 26% by mass. If the content of CaO relative to the total amount of glass fiber is less than 14% by mass, the viscosity of the molten glass becomes high, and therefore, there is a tendency for the productivity of the glass fiber to decrease. On the other hand, if the content of CaO relative to the total amount of glass fiber exceeds 32% by mass, crystallization is easily generated in the glass filaments constituting the glass fiber during the manufacturing process of the glass fiber, and there is a tendency for the productivity of the glass fiber to decrease.

[0062] In addition, the glass composition of the glass fiber of the present embodiment may have other components in addition to SiO2 and CaO. The other components are not particularly limited, and examples thereof include Al2O3 and MgO.

[0063] In the glass fiber of the present embodiment, the content of each component can be measured by using an ICP emission spectrometer to measure Li as a light element, and a wavelength dispersive X-ray fluorescence analyzer to measure the content of other elements.

[0064] As a measuring method, the following method can be cited: first, a glass batch is placed in a platinum crucible, and is kept at a temperature of 1550° C. for 4 hours and at a temperature of 1650° C. for 2 hours in an electric furnace, and is melted while being stirred, thereby obtaining a homogeneous molten glass. Alternatively, a glass fiber is placed in a platinum crucible, and is kept at a temperature of 1600° C. for 4 hours in an electric furnace, and is melted while being stirred, thereby obtaining a homogeneous molten glass.

[0065] The glass batch material is a raw material for forming the glass fiber or the glass filament constituting the glass fiber, and the glass batch material is prepared by mixing glass raw materials in a manner that will become a glass composition for glass fiber having a desired composition. In addition, in the case where organic matter is attached to the surface of the glass fiber of the glass fiber, or the glass fiber is mainly contained in the organic matter (resin) as a reinforcing material, the glass fiber is used after removing the organic matter, for example, by heating in a muffle furnace at a temperature range of 300 to 650° C. for a time range of about 0.5 to 24 hours.

[0066] Next, the obtained molten glass is poured onto a carbon plate to form glass chips, and the glass chips are then crushed into powder to obtain glass powder.

[0067] Next, after the glass powder is heated and decomposed with an acid, Li as a light element is quantitatively analyzed using an ICP emission spectrophotometer. After the glass powder is formed into a disc shape using a press, other elements are quantitatively analyzed using a wavelength dispersive fluorescence X-ray analyzer. In the quantitative analysis using a wavelength dispersive fluorescence X-ray analyzer, specifically, a calibration curve sample can be prepared based on the results measured by the fundamental parameter method, and quantitative analysis can be performed using a standard curve method. It should be noted that the content of each component in the calibration curve sample can be quantitatively analyzed using an ICP emission spectrophotometer. These quantitative analysis results are converted into oxides, the content and total amount of each component are calculated, and the content (mass %) of each component can be calculated based on these numerical values.

[0068] As a preferred form of the glass fiber (also referred to as glass fiber bundle or glass strand) contained in the glass fiber reinforced thermoplastic resin material of the present embodiment before molding, the following chopped strands can be cited: the number of glass filaments constituting the glass fiber (the number of bundled strands) is within a specified range and is cut into a specified length range. In the above-mentioned chopped strands, the number of glass filaments constituting the glass fiber is preferably in the range of 1 to 20,000, more preferably in the range of 50 to 10,000, and further preferably in the range of 1,000 to 8,000. In addition, in the chopped strands, the cut length of the glass fiber is preferably in the range of 1.0 to 100.0 mm, more preferably in the range of 1.2 to 51.0 mm, further preferably in the range of 1.5 to 30.0 mm, particularly preferably in the range of 2.0 to 15.0 mm, and most preferably in the range of 2.3 to 7.8 mm.

[0069] In addition, as the form of the glass fiber contained in the glass fiber reinforced thermoplastic resin material of this embodiment before the molding process, in addition to chopped strands, roving and cut fibers can also be cited. The roving has a form in which the number of glass filaments constituting the glass fiber is within the range of 10 to 30,000 without being cut. In addition, the cut fibers have the following form: the glass filaments constituting the glass fiber within the range of 1 to 20,000 are crushed into a length range of 0.001 mm to 0.900 mm by a known method such as a ball mill or a Henschel mixer.

[0070] In order to improve the adhesion between glass fiber and resin, improve the uniform dispersibility of glass fiber in the mixture of glass fiber and resin, etc., the surface of glass fiber contained in the glass fiber reinforced thermoplastic resin material of the present embodiment can be coated with organic matter. As such organic matter, resins such as polyurethane resin, epoxy resin, vinyl acetate resin, acrylic resin, modified polypropylene (especially carboxylic acid modified polypropylene), copolymers of (poly) carboxylic acid (especially maleic acid) and unsaturated monomers, or silane coupling agents can be cited.

[0071] In addition, the glass fiber contained in the glass fiber reinforced thermoplastic resin material of the present embodiment may be coated with a composition including a lubricant, a surfactant, etc., in addition to being coated with these resins or silane coupling agents. The composition coats the glass fiber in a ratio range of 0.1 to 2.0 mass % based on the mass of the glass fiber in a state not coated with the composition.

[0072] Here, examples of the silane coupling agent include aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, acrylic silane, and cationic silane.

[0073] Examples of the aminosilane include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N′-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.

[0074] Examples of the chlorosilane include γ-chloropropyltrimethoxysilane.

[0075] Examples of the epoxysilane include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0076] Examples of the mercaptosilane include γ-mercaptotrimethoxysilane and the like.

[0077] Examples of the vinyl silane include vinyltrimethoxysilane and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane.

[0078] Examples of the cationic silane include N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride and N-phenyl-3-aminopropyltrimethoxysilane hydrochloride.

[0079] In the present embodiment, the silane coupling agent may be used alone or in combination of two or more thereof.

[0080] Examples of lubricants include modified silicone oil, animal oils and their hydrogenates, vegetable oils and their hydrogenates, animal waxes, vegetable waxes, mineral waxes, condensates of higher saturated fatty acids and higher saturated alcohols, polyethyleneimine, polyalkylpolyamine alkyl linolenic acid derivatives, fatty acid amides, quaternary ammonium salts, and the like.

[0081] Examples of the animal oil include beef tallow and the like.

[0082] Examples of the vegetable oil include soybean oil, coconut oil, rapeseed oil, palm oil, and castor oil.

[0083] Examples of the animal wax include beeswax and lanolin.

[0084] Examples of the vegetable wax include candelilla wax and carnauba wax.

[0085] Examples of the mineral wax include paraffin wax and montan wax.

[0086] Examples of the condensate of the higher saturated fatty acid and the higher saturated alcohol include stearic acid esters such as lauryl stearate.

[0087] Examples of the fatty acid amide include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, and fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.

[0088] Examples of the quaternary ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.

[0089] In the present embodiment, the above lubricants may be used alone or in combination of two or more.

[0090] Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants.

[0091] Examples of the nonionic surfactant include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene-block copolymer ethers, alkyl polyoxyethylene-polyoxypropylene-block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, polyoxyethylene stearyl ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyhydric alcohol alkyl ethers, fatty acid alkanolamides, acetylene glycols, ethylene oxide adducts of acetylene glycols, and ethylene oxide adducts of acetylene alcohols.

[0092] Examples of the cationic surfactant include alkyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, alkyldimethylethylammonium ethylsulfate, higher alkylamine acetates, higher alkylamine hydrochlorides, ethylene oxide adducts of higher alkylamines, condensates of higher fatty acids and polyalkylene polyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline-type cationic surfactants, alkylpyridinium salts, and the like.

[0093] Examples of the anionic surfactant include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.

[0094] Examples of the amphoteric surfactant include amino acid-type amphoteric surfactants such as alkylaminopropionic acid alkali metal salts, betaine-type amphoteric surfactants such as alkyldimethylbetaine, and imidazoline-type amphoteric surfactants.

[0095] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the above-mentioned metal material is preferably an aluminum material, an aluminum alloy or stainless steel. As the above-mentioned aluminum material, for example, A1050 and A1100 can be cited. As the above-mentioned aluminum alloy, A1200, A2017, A2024, A3003, A3004, A4032, A5005, A5052, A5083, A6061, A6063, A7075, etc. can be cited. In addition, as the above-mentioned stainless steel, for example, SUS301, SUS304, SUS316, SUS316L, etc. can be cited. Considering that the heat cycle resistance can be greatly improved, the above-mentioned metal material is more preferably an aluminum material or an aluminum alloy.

[0096] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the absolute value of the difference between the linear expansion coefficient of the metal material and the average linear expansion coefficient of the glass fiber reinforced thermoplastic resin material is, for example, 4.5×10 -5 In addition, considering that the heat cycle resistance can be greatly improved, the absolute value of the difference between the linear expansion coefficient of the metal material and the average linear expansion coefficient of the glass fiber reinforced thermoplastic resin material is preferably 3.0×10 -5 / °C or less. Here, the linear expansion coefficient of the above-mentioned metal material can be measured in accordance with JIS Z 2285: 2003. In addition, the average linear expansion coefficient of the above-mentioned glass fiber reinforced thermoplastic resin material can be obtained by measuring the linear expansion coefficient in the flow direction (MD direction) and the linear expansion coefficient in the direction perpendicular to the MD direction (TD direction) of the flat test piece in accordance with JIS K 7197: 2012, and obtaining the average value of the above-mentioned linear expansion coefficients.

[0097] In the metal-glass fiber reinforced thermoplastic resin composite material of this embodiment, the entire surface or a portion of the surface of the metal material in contact with the glass fiber reinforced thermoplastic resin material is preferably roughened by a known method to provide a concavo-convex effect.

[0098] In addition, in the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, examples of the thermoplastic resin contained in the above-mentioned glass fiber reinforced thermoplastic resin material include: polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorinated polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), Polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polycarbonate, polyarylene sulfide, polyethersulfone (PES), polyphenylsulfone (PPSU), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyaryletherketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PEI), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutene, polymethylpentene, olefin / vinyl alcohol resin, cyclic olefin resin, cellulose resin, polylactic acid, etc.

[0099] Specifically, examples of polyethylene include high-density polyethylene (HDPE), medium-density polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.

[0100] Examples of the polypropylene include isotactic polypropylene, atactic polypropylene, syndiotactic polypropylene, and mixtures thereof.

[0101] Examples of the polystyrene include general-purpose polystyrene (GPPS) which is atactic polystyrene having an atactic structure, high impact polystyrene (HIPS) obtained by adding a rubber component to GPPS, and syndiotactic polystyrene having a syndiotactic structure.

[0102] Examples of the methacrylic resin include polymers obtained by polymerizing one of the following components alone or two or more of the following components: acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and fatty acid vinyl ester.

[0103] Examples of polyvinyl chloride include homopolymers of vinyl chloride polymerized by conventionally known methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, and bulk polymerization, copolymers of vinyl chloride monomers and copolymerizable monomers, and graft copolymers in which vinyl chloride monomers are grafted onto polymers.

[0104] Examples of the polyamide include one of the following components or a copolymer of two or more components or a mixture thereof: polycaprolactam (polyamide 6), polyhexamethylene adipamide (polyamide 66), polybutylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 410), polyheptamethylene adipamide (polyamide 56), polypentamethylene sebacamide (polyamide 510), polyhexamethylene sebacamide (polyamide 610), polydodecanoic acid hexamethylene diamine ... amine (polyamide 612), polydecanediamine adipamide (polyamide 106), polydecanediamine sebacate (polyamide 1010), polydecanediamine dodecanediamine (polyamide 1012), polyundecanamide (polyamide 11), polyundecanamide adipamide (polyamide 116), polydodecaneamide (polyamide 12), polyphenylene adipamide (polyamide XD6), polyphenylene adipamide (polyamide XD10), polym-phenylene adipamide (polyamide MXD6 ), polyphenylene adipamide (polyamide PXD6), polybutylene terephthalamide (polyamide 4T), polypentamethylene terephthalamide (polyamide 5T), polyhexamethylene terephthalamide (polyamide 6T), polyhexamethylene isophthalamide (polyamide 6I), polynonane terephthalamide (polyamide 9T), polydecane terephthalamide (polyamide 10T), polyundecanediamine terephthalamide (polyamide 11T), polydodecane terephthalamide (polyamide 12 T), polybutylene isophthalamide (polyamide 4I), polybis(3-methyl-4-aminohexyl)methane terephthalamide (polyamide PACMT), polybis(3-methyl-4-aminohexyl)methane isophthalamide (polyamide PACMI), polybis(3-methyl-4-aminohexyl)methane dodecanedioamide (polyamide PACM12), polybis(3-methyl-4-aminohexyl)methane tetradecanedioamide (polyamide PACM14), etc.

[0105] From the viewpoint of low water absorption and excellent dimensional accuracy, the polyamide is preferably a long-chain polyamide. In the long-chain polyamide, the average number of carbon atoms per nitrogen atom is more than 9 and less than 30, for example, polyamide 11, polyamide 12, polyamide 1010, polyamide 1012, etc. can be cited.

[0106] Examples of the polyacetal include a homopolymer having an oxymethylene unit as a main repeating unit and a copolymer mainly composed of an oxymethylene unit and containing an oxyalkylene unit having 2 to 8 adjacent carbon atoms in the main chain.

[0107] Examples of polyethylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with ethylene glycol, and the like.

[0108] Examples of the polybutylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with 1,4-butanediol, and the like.

[0109] Examples of the polytrimethylene terephthalate include polymers obtained by polycondensing terephthalic acid or a derivative thereof with 1,3-propylene glycol, and the like.

[0110] Examples of the polycarbonate include polymers obtained by an ester exchange method in which a dihydroxydiaryl compound is reacted with a carbonate such as diphenyl carbonate in a molten state, and polymers obtained by a phosgene method in which a dihydroxydiaryl compound is reacted with phosgene.

[0111] Examples of the polyarylene sulfide include linear polyphenylene sulfide, cross-linked polyphenylene sulfide that has a high molecular weight by a curing reaction after polymerization, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.

[0112] Examples of the polyphenylene ether include poly(2,3-dimethyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-chloromethyl-1,4-phenylene ether), poly(2-methyl-6-hydroxyethyl-1,4-phenylene ether), poly(2-methyl-6-n-butyl-1,4-phenylene ether), poly(2-ethyl-6-isopropyl-1,4-phenylene ether), poly(2-ethyl-6-n-propyl-1,4-phenylene ether), poly(2,3,6-trimethyl-1,4-phenylene ether), poly[2-(4'-methylphenyl)-1,4-phenylene ether], poly(2-bromo-6-phenyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2-phenyl 4-phenylene ether), poly(2-chloro-1,4-phenylene ether), poly(2-methyl-1,4-phenylene ether), poly(2-chloro-6-ethyl-1,4-phenylene ether), poly(2-chloro-6-bromo-1,4-phenylene ether), poly(2,6-di-n-propyl-1,4-phenylene ether), poly(2-methyl-6-isopropyl-1,4-phenylene ether), poly(2-chloro-6-methyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dibromo-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2,6-dimethyl-1,4-phenylene ether), and the like.

[0113] Examples of the modified polyphenylene ether include polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / maleic anhydride copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polyamides, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene / acrylonitrile copolymers, modified polyphenylene ethers in which functional groups such as amino groups, epoxy groups, carboxyl groups, and styryl groups are introduced into polymer chain terminals of the above polyphenylene ethers, and modified polyphenylene ethers in which functional groups such as amino groups, epoxy groups, carboxyl groups, styryl groups, and methacryloyl groups are introduced into polymer chain side chains of the above polyphenylene ethers.

[0114] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK), etc. From the viewpoint of market availability and cost, polyetheretherketone is preferably used as the polyaryletherketone.

[0115] Examples of liquid crystal polymers (LCP) include (co)polymers composed of one or more structural units selected from aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, etc., which are thermotropic liquid crystal polyesters.

[0116] Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylene / chlorotrifluoroethylene resin (ECTFE).

[0117] Examples of the ionomer (IO) resin include copolymers of olefins or styrene and unsaturated carboxylic acids, and polymers in which a part of the carboxyl groups is neutralized with metal ions.

[0118] Examples of the olefin / vinyl alcohol resin include ethylene / vinyl alcohol copolymers, propylene / vinyl alcohol copolymers, ethylene / vinyl acetate copolymer saponification products, and propylene / vinyl acetate copolymer saponification products.

[0119] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclopentadiene, and polymers of cyclic olefin monomers.

[0120] Examples of the polylactic acid include poly-L-lactic acid which is an L-form homopolymer, poly-D-lactic acid which is a D-form homopolymer, and stereocomplex polylactic acid which is a mixture thereof.

[0121] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, cellulose propionate, and cellulose butyrate.

[0122] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, from the viewpoints of mechanical properties, heat resistance, dielectric properties, chemical resistance, and productivity (molding temperature and fluidity), the thermoplastic resin contained in the above-mentioned glass fiber reinforced thermoplastic resin material is preferably a thermoplastic resin selected from the group consisting of polyphenylene sulfide, polyamide, polybutylene terephthalate, and polyaryletherketone, and from the viewpoint of ease of use, the thermoplastic resin is preferably a thermoplastic resin selected from the group consisting of polyphenylene sulfide, polyamide, and polybutylene terephthalate. From the viewpoint of being able to greatly improve heat cycle resistance, the above-mentioned thermoplastic resin is further preferably polybutylene terephthalate or polyphenylene sulfide, and is particularly preferably polyphenylene sulfide. In addition, from the viewpoint that heat cycle resistance can be greatly improved and the value of bonding strength is high, the above-mentioned thermoplastic resin is particularly preferably polybutylene terephthalate.

[0123] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the glass fiber reinforced thermoplastic resin material may also contain components other than the glass fiber and the thermoplastic resin, provided that the purpose of the present invention is not hindered. Such components include: reinforcing fibers other than the glass fiber, fillers other than the glass fiber, flame retardants, ultraviolet absorbers, heat stabilizers, antioxidants, antistatic agents, flow improvers, anti-blocking agents, lubricants, nucleating agents, antibacterial agents, pigments, etc.

[0124] Examples of reinforcing fibers other than the glass fibers include carbon fibers, metal fibers, etc. Examples of fillers other than the glass fibers include glass powder, talc, mica, and the like.

[0125] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the glass fiber reinforced thermoplastic resin material may contain the above components in an amount ranging from 0 to 40% by mass based on the total amount of the glass fiber reinforced thermoplastic resin material.

[0126] In the metal-glass fiber reinforced thermoplastic resin composite material of the present embodiment, the glass fiber reinforced thermoplastic resin material may be located on, for example, the upper surface, the lower surface, or both surfaces of the thin plate-shaped metal material. In addition, the glass fiber reinforced thermoplastic resin material may be located at a position in contact with the entire surface of any one surface of the metal material, or may be located at a position in contact with a portion of any one surface of the metal material.

[0127] Examples of uses of the metal-glass fiber reinforced thermoplastic resin composite material of this embodiment include: casings, frames and other accessories of portable electronic devices represented by smartphones, automotive electrical components such as battery tray covers, sensors, coil skeletons, electronic and electrical components other than portable electronic devices, and electrical connection terminal accessories.

[0128] Next, examples of the present invention and comparative examples are shown.

[0129] Example

[0130] [Examples 1 to 9]

[0131] Resin pellets were prepared in the following manner: glass fibers (chopped strands) and polyphenylene sulfide (manufactured by Kureha Co., Ltd., trade name: FORTRON KPSW-203A, described as "PPS" in Table 1) were mixed at a screw speed of 100 rpm using a twin-shaft mixer (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) so that the resin pellets had a glass content C as shown in Table 1, wherein the glass fibers had a SiO2 content, a CaO content, a Vickers hardness, a short diameter, a long diameter, a 500-poise temperature, and a 10,000-poise temperature as shown in Table 1, and the cut length was 3 mm.

[0132] It should be noted that in Table 1, the SiO2 content and the CaO content are ratios relative to the total amount of the glass fibers, and the minor axis and the major axis are the minor axis and the major axis of the glass filaments constituting the glass fibers.

[0133] Next, stainless steel (S50C, indicated as "SUS" in Table 1) processed into a prism of 14 mm × 14 mm × 25 mm was set in a mold of an injection molding machine (manufactured by Sodick Co., Ltd., trade name: VRE40), and the resin pellets of Examples 1 to 9 were respectively put into the hopper of the injection molding machine heated to 310° C. to perform insert molding. As a result, a metal-glass fiber reinforced thermoplastic resin composite material in which the glass fiber reinforced thermoplastic resin material of 21.8 mm × 21.8 mm × 21.8 mm in Examples 1 to 9 was located on the surface of 14 mm × 14 mm of the stainless steel was obtained.

[0134] Next, the heat cycle resistance, glass fiber productivity, and flexural strength, which is an index of mechanical strength of the glass fiber reinforced thermoplastic resin material, of the metal-glass fiber reinforced thermoplastic resin composite materials of Examples 1 to 9 were evaluated in the following manner.

[0135] [Heat cycle resistance of metal-glass fiber reinforced thermoplastic resin composites]

[0136] A low-temperature resistance test was conducted with the following steps as one cycle: the metal-glass fiber reinforced thermoplastic resin composite materials of Examples 1 to 9 were placed at -40°C for 30 minutes, then heated to 180°C, and placed at 180°C for 30 minutes before being cooled to -40°C again. In the above low-temperature resistance test, whether the interface between the metal material and the glass fiber reinforced thermoplastic resin material was damaged was investigated in units of 24 cycles, thereby evaluating the heat cycle resistance of the metal-glass fiber reinforced thermoplastic resin composite material.

[0137] Regarding the evaluation of the above-mentioned heat cycle resistance, in the above-mentioned low and high temperature resistance test, the case where damage occurred at the above-mentioned interface after 48 cycles was evaluated as "×", the case where damage occurred in the range of more than 48 cycles to less than 168 cycles was evaluated as "0", and the case where no damage occurred after 168 cycles was evaluated as "◎".

[0138] In addition, the above “◎” represents excellent, “○” represents good, and “×” represents poor.

[0139] 〔Productivity of glass fiber〕

[0140] A glass batch prepared by mixing glass raw materials in a manner that can form the glass composition of Examples 1 to 9 is placed in a platinum crucible, and is kept at a temperature of 1650° C. in an electric furnace for 6 hours, and is melted while being stirred, thereby obtaining a homogeneous molten glass. Next, the molten glass is poured onto a carbon plate to produce glass scraps. Then, the glass scraps are placed in a platinum container, and the platinum container is heated to a temperature range of 1200 to 1450° C. to melt the glass scraps.

[0141] Next, the obtained molten glass was pulled out from the nozzle head of the above-mentioned platinum container and wound on a winder, and the winder was rotated at a rotation speed of 1100 rpm to wind the molten glass for 1 hour, thereby spinning. At this time, the evaluation of the productivity of the glass fiber was evaluated as "◎" when the spinning could be carried out continuously without breaking within 1 hour, "0" when the number of breaks within 1 hour was 1 to 2 times and the spinning could be carried out continuously for more than 30 minutes, and "×" when the other cases were evaluated.

[0142] In addition, the above “◎” represents excellent, “○” represents good, and “×” represents poor.

[0143] [Flexural strength of glass fiber reinforced thermoplastic resin materials]

[0144] The resin pellets obtained in Examples 1 to 9 were injection molded using an injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., trade name: NEX80) at a mold temperature of 90° C. and an injection temperature of 270° C. to prepare A-type dumbbell test pieces (thickness 4 mm) in accordance with JIS K7165:2008. The measured values ​​of the A-type dumbbell test pieces were measured by a static tensile test in accordance with JIS K 7171:2016 using a precision universal testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000B) at a test temperature of 23° C., and the flexural strength of the glass fiber reinforced thermoplastic resin material was determined.

[0145] [Examples 10 to 16]

[0146] Resin pellets were prepared in the following manner: glass fibers (chopped strands) and polybutylene terephthalate (manufactured by Polyplastics Co., Ltd., trade name: DURANEX 2000, recorded as "PBT" in Table 2) were mixed at a screw speed of 100 rpm using a twin-shaft mixer (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) so that the resin pellets had a glass content C as shown in Table 2, wherein the glass fibers had a SiO2 content, a CaO content, a Vickers hardness, a short diameter, a long diameter, a 500-poise temperature, and a 10,000-poise temperature as shown in Table 2, and a cut length of 3 mm. Except for this, the metal-glass fiber reinforced thermoplastic resin composite materials of Examples 10 to 16 were prepared in exactly the same manner as Examples 1 to 9.

[0147] It should be noted that in Table 2, the SiO2 content and the CaO content are ratios relative to the total amount of the glass fibers, and the minor axis and the major axis are the minor axis and the major axis of the glass filaments constituting the glass fibers.

[0148] Next, the heat cycle resistance, glass fiber productivity, and flexural strength, which is an index of mechanical strength of the glass fiber reinforced thermoplastic resin material, of the metal-glass fiber reinforced thermoplastic resin composite materials of Examples 10 to 16 were evaluated in exactly the same manner as in Examples 1 to 9. The results are shown in Table 2.

[0149] [Example 17]

[0150] The metal-glass fiber reinforced thermoplastic resin composite material of Example 17 was prepared in exactly the same manner as in Example 1, except that an aluminum alloy (A5052, marked as "ALU" in Table 3) processed into prisms of 14 mm × 14 mm × 25 mm was used instead of stainless steel processed into prisms of 14 mm × 14 mm × 25 mm.

[0151] Next, the heat cycle resistance, glass fiber productivity, and flexural strength, which is an index of mechanical strength of the glass fiber reinforced thermoplastic resin material, of the metal-glass fiber reinforced thermoplastic resin composite material of Example 17 were evaluated in exactly the same manner as in Examples 1 to 9. The results are shown in Table 3.

[0152] [Comparative Examples 1 to 7]

[0153] Resin pellets were prepared in the following manner: glass fibers (chopped strands) and polyphenylene sulfide (manufactured by Kureha Co., Ltd., trade name: FORTRON KPSW-203A, marked as "PPS" in Table 4) were kneaded at a screw speed of 100 rpm using a twin-screw kneader (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) so that the resin pellets had a glass content C shown in Table 4, wherein the glass fibers had a SiO2 content, a CaO content, a Vickers hardness, a short diameter, a long diameter, a 500 poise temperature, and a 10,000 poise temperature shown in Table 4, and a cut length of 3 mm. Except for this, the metal-glass fiber reinforced thermoplastic resin composite materials of Comparative Examples 1 to 7 were prepared in exactly the same manner as Examples 1 to 9.

[0154] It should be noted that in Table 4, the SiO2 content and the CaO content are ratios relative to the total amount of the glass fibers, and the minor axis and the major axis are the minor axis and the major axis of the glass filaments constituting the glass fibers.

[0155] Next, the heat cycle resistance, glass fiber productivity, and flexural strength, which is an index of mechanical strength of the glass fiber reinforced thermoplastic resin material, of the metal-glass fiber reinforced thermoplastic resin composite materials of Comparative Examples 1 to 7 were evaluated in exactly the same manner as in Examples 1 to 9. The results are shown in Table 4.

[0156] [Comparative Examples 8 to 14]

[0157] Resin pellets were prepared in the following manner: glass fibers (chopped strands) and polybutylene terephthalate (manufactured by Polyplastics Co., Ltd., trade name: DURANEX 2000, marked as "PBT" in Table 5) were mixed at a screw speed of 100 rpm using a twin-shaft mixer (manufactured by Shibaura Machine Co., Ltd., trade name: TEM-26SS) so that the resin pellets had a glass content C as shown in Table 5, wherein the glass fibers had a SiO2 content, a CaO content, a Vickers hardness, a short diameter, a long diameter, a 500-poise temperature, and a 10,000-poise temperature as shown in Table 5, and a cut length of 3 mm. Except for this, the metal-glass fiber reinforced thermoplastic resin composite materials of Comparative Examples 8 to 14 were prepared in exactly the same manner as in Examples 1 to 9.

[0158] It should be noted that in Table 5, the SiO2 content and the CaO content are ratios relative to the total amount of the glass fiber, and the minor axis and the major axis are the minor axis and the major axis of the glass filaments constituting the glass fiber.

[0159] Next, the heat cycle resistance, glass fiber productivity, and flexural strength, which is an index of mechanical strength of the glass fiber reinforced thermoplastic resin material, of the metal-glass fiber reinforced thermoplastic resin composite materials of Comparative Examples 8 to 14 were evaluated in exactly the same manner as in Examples 1 to 9. The results are shown in Table 5.

[0160] [Table 1]

[0161]

[0162] [Table 2]

[0163]

[0164] [Table 3]

[0165]

[0166] [Table 4]

[0167]

[0168] [Table 5]

[0169]

[0170] The metal-glass fiber reinforced thermoplastic resin composite materials of Examples 1 to 16, in which the difference ΔT (ΔT=T1-T2) between the temperature T2 and the temperature T2 is in the range of 157 to 186°C, the ratio of the major axis to the minor axis (major axis / minor axis) A of the above-mentioned glass filaments is in the range of 1.5 to 4.5, and the glass content C of the above-mentioned glass fiber reinforced thermoplastic resin material is in the range of 20.0 to 65.0% by mass, have high productivity of glass fibers and mechanical strength of glass fiber reinforced thermoplastic resin materials, and have excellent heat cycle resistance between metal materials and glass fiber reinforced thermoplastic resin materials.

[0171] On the other hand, it is obvious from Tables 4 and 5 that for the metal-glass fiber reinforced thermoplastic resin composite materials of Comparative Examples 1 to 14, in which any one or more of the parameters including the difference ΔT (ΔT=T1-T2) between the 500-poise temperature T1 and the 10,000-poise temperature T2, the ratio of the major axis to the minor axis (major axis / minor axis) A of the above-mentioned glass fiber, or the glass content C of the above-mentioned glass fiber reinforced thermoplastic resin material is outside the above-mentioned range, any one of the indicators including the productivity of the glass fiber, the mechanical strength of the glass fiber reinforced thermoplastic resin material, or the heat cycle resistance between the metal material and the glass fiber reinforced thermoplastic resin material is insufficient.

[0172] It should be noted that in Example 1, the absolute value of the difference between the linear expansion coefficient of the metal material and the average linear expansion coefficient of the glass fiber reinforced thermoplastic resin material is 3.6×10 -5 / °C, and in the evaluation of the heat cycle resistance, the failure was confirmed after 360 cycles. On the other hand, in Example 17, the absolute value of the difference between the linear expansion coefficient of the metal material and the average linear expansion coefficient of the glass fiber reinforced thermoplastic resin material was 2.4×10 -5 / °C, and in the evaluation of the heat cycle resistance, no destruction was observed even after 480 cycles.

Claims

1. A metal-glass fiber reinforced thermoplastic resin composite material, comprising a metal material and a glass fiber reinforced thermoplastic resin material located on at least one surface of the metal material, The metal-glass fiber reinforced thermoplastic resin composite material is characterized in that: The difference ΔT between the 500 poise temperature T1 and the 10000 poise temperature T2 of the glass fiber contained in the glass fiber reinforced thermoplastic resin material, that is, ΔT=T1-T2, is in the temperature range of 157 to 186°C. The glass filaments constituting the glass fiber have a flat cross-sectional shape in which the ratio of the major diameter to the minor diameter (major diameter / minor diameter) A of the glass filaments is in the range of 1.5 to 4.

5. The glass content C of the glass fiber reinforced thermoplastic resin material is in the range of 20.0 to 65.0% by mass.

2. The metal-glass fiber reinforced thermoplastic resin composite material according to claim 1, characterized in that: The glass fiber contained in the glass fiber reinforced thermoplastic resin material has a Vickers hardness H in the range of 700 to 800 HV0.2, and A, C, ΔT and H satisfy the following formula (1): 6.53≤H×C 1 / 2 / (A×ΔT)≤13.45 … (1)。 3. The metal-glass fiber reinforced thermoplastic resin composite material according to claim 2, characterized in that: The A, C, ΔT and H satisfy the following formula (2): 5.72≤H×C 1 / 2 / (A×ΔT)≤9.83 … (2)。 4. The metal-glass fiber reinforced thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin contained in the glass fiber reinforced thermoplastic resin material is a thermoplastic resin selected from the group consisting of polyphenylene sulfide, polyamide, polybutylene terephthalate, and polycarbonate.

Citation Information

Patent Citations

  • Insert molded product

    JP2005161693A

  • Resin metal composite body and method for producing same

    WO2020004597A1

  • Enclosure for electronic apparatus and method of manufacturing the same

    JP2009267313A

  • Glassfiber reinforced thermoplastic composition and molding thereof

    JP2015105359A

  • Resin metal composite body and method for producing same

    US20210268771A1